Durability of percutaneous transluminal angioplasty for failing hemodialysis vascular access, retrospective cohort study. (2020) - Alhaizaey, Abdullah; Alghamdi, Musaad; Azazy, Ahmed; Omran, Walid; Hamdy, Mohammed; Alhazmi, Barrag; Karmotah, Ahmed
Abstract: Objective: The arteriovenous fistula (AVF) is the preferred access type for hemodialysis, owing to its better patency rates and fewer complications. This study aimed to evaluate the outcome of percutaneous transluminal angioplasty in a failing arteriovenous fistula and arteriovenous graft in hemodialysis patients. Methods: Clinical data of patients who underwent percutaneous transluminal angioplasty in the vascular department of Aseer Central Hospitals, KSA, from January 2017 to May 2018 and with follow-up of >12 months were analyzed in retrospective cohort study. Results: Angioplasties were performed in 55 patients with fistulae, of which 18 patients had venous hypertension on dialysis and the remaining patients had weak or poor flow. Conclusions: Percutaneous transluminal angioplasty is an efficacious method for the correction of stenosis of arteriovenous fistulae for patients on hemodialysis, prolonging the patency of the fistula and enabling new interventions. Highlights: Angioplasty is an efficacious for correction of stenosis of arteriovenous fistulae. Results comparable to open surgery are obtained with less trauma to the patient. Open surgery should be reserved for non-salvageable fistulas.